EVALUASI BADAN LEGISLASI DPRD PROVINSI JAWA TENGAH 2009-2014 - WAHID ABDULRAHMAN (Politika: Jurnal Ilmu Politik, 2016)
AbstractRegional Legislation Board as one of the fittings of regional house of representative that has a vital role for the implementation of the legislative function which is owned by the local parliament. The board then was changed to the Establishment of regional regulation board as the revision of Law on Local Government number 32 of 2014 to Law number 23 of 2014. Using  qualitative research approach this research focused on how the performance of the Legislative Board of Central Java house of representative from 2009 to 2014. Results of this study indicated that in general the Legislation Board has done a good job in preparing the Local Legislation Program, assessment or harmonisation on local regulations proposed draft. However, these functions had not been able to be implemented effectively and efficiently in the absence of guidelines standard for the tasks implementation. It can be seen from long distant between the assessment of the proposal with other proposals because of not having a clear standard. Even when the assessment conducted by the Legislation Board often exceeded the time limit determined by the central java house of representative leaders.Key Words : Legislation Board, legislation function